A Reliability Improved Routing as a Qos Measure for Mobile Ad-Hoc Networks - Abdulkadhim, Mustafa; A.Mohammed Ali, Salim; Hasan, sami (International Journal of Engineering and Technology, 2018)
In the recent time, the huge expansion in the application of the real-time applications for smartphones resulted in new difficulties when it is time to develop new protocols for mobile ad-hoc networks (MANETS). Most important within these difficulties is to activate real-time applications for mobile ad-hoc networks which includes quality of service (QoS) support, like bandwidth constraints and stability issues. Adding to this of course the reliability of the nodes as an important factor that has a direct effect on the network performance and data integrity.In this paper we will discussed the QoS main issue that affect several factors in the mobile ad hoc networks, which is the reliability. Because of the fact that the reliability and the availability of the nodes can be interacted made me use both the terms throughout the paper. we will suggest the efficient multi-path Quality of service routing (EMQR), (EMQR) as a QoS guarantee for the stability and reliability issues in the network. Next, we will discuss the availability issues as a QoS guarantee and for this we will suggest the best suitable protocol which is â€œan efficient warning energy aware Cluster headâ€ WEAC as a solution to the availability issue.The two protocols will guarantee the availability and the reliability in MANETs as it is the new direction for routing algorithms design and it is a way to enhance the availability by controlling the Cluster head based on its power level as a metric for availability as in WEAC protocol and the reliability by increasing the reserved bandwidth for the route as mentioned in EMQR protocol.Â Â